Introduction to hand hygiene - HSTN (Carrollton, Tx : Primedia Healthcare, 2002)
(Producer) Introduces the concept of hand hygiene and how it relates to infection control. Why some people don't practice good hand hygiene is explored along with some of the waterless antiseptics that are now available
VHS
Keywords: Handwashing; Infection control